Predictive Value of Electromechanical Activation Time for In-Hospital Major Cardiac Adverse Events in Heart Failure Patients - Jing Zhang; Wen-Xian Liu; Shu-Zheng Lyu (Cardiovascular Therapeutics)
Objective. This prospective study aimed to evaluate the value of the cardiac cycle time-corrected electromechanical activation time (EMATc) measured at admission for predicting major cardiac adverse events (MACEs) in hospitalized patients with chronic heart failure (CHF). Methods. CHF patients with a left ventricular ejection fraction (LVEF) lower than 50% N=145 were enrolled in this study. Documented clinical end-points (MACEs) included cardiogenic death, onset of acute HF as assessed with invasive and noninvasive mechanical ventilation, and cardiogenic shock. According to the different clinical end-points, patients were divided into two groups: a MACE group n=22 and a nonMACE group n=123. EMATc, LVEF, and circulating levels of B type natriuretic peptide (BNP) and Troponin I (TnI) were measured. Multivariate logistic regression analysis was used to examine the association between EMATc and MACEs. The parameters adjusted in the multivariable model included EMATc, BNP, and heart rate. The predictive value of EMATc was evaluated by receiver operating characteristic (ROC) curve analysis. Results. Elevated EMATc was an independent risk factor for MACEs (odds ratio [OR] 1.1443, 95% confidence interval [CI] 1.016–1.286, P=0.027). The area under the ROC curve for EMATc was 0.799 (95% CI 0.702–0.896, P<0.001). The optimal cutoff EMATc value was >13.8% with a sensitivity of 81.8% and a specificity of 65.9%. Conclusions. We demonstrated that an elevated EMATc measured at admission is an independent risk factor for MACEs among hospitalized CHF patients. Acoustic cardiography measured at admission may provide a simple, noninvasive method for risk stratification of CHF patients. This trial is registered with ChiCTR1900021470.